The phylogeny of the superfamily Coccoidea (Hemiptera: Sternorrhyncha) based on the morphology of extant and extinct macropterous males. (22nd August 2013) - HODGSON, CHRIS J.; HARDY, NATE B.
Abstract Currently, 49 families of scale insects are recognised, 33 of which are extant. Despite more than a decade of DNA sequence‐based phylogenetic studies of scales insects, little is known with confidence about relationships among scale insects families. Multiple lines of evidence support the monophyly of a group of 18 scale insect families informally referred to as the neococcoids. Among neococcoid families, published DNA sequence‐based estimates have supported Eriococcidae paraphyly with respect to Beesoniidae, Dactylopiidae, and Stictococcidae. No other neococcoid interfamily relationship has been strongly supported in a published study that includes exemplars of more than ten families. Likewise, no well‐supported relationships among the 15 extant scale insect families that are not neococcoids (usually referred to as 'archaeococcoids') have been published. We use a Bayesian approach to estimate the scale insect phylogeny from 162 adult male morphological characters, scored from 269 extant and 29 fossil species representing 43/49 families. The result is the most taxonomically comprehensive, most resolved and best supported estimate of phylogenetic relationships among scale insect families to date. Notable results include strong support for (i) Ortheziidae sister to Matsucoccidae, (ii) a clade comprising all scale insects except for Margarodidae s.s., Ortheziidae and Matsucoccidae, (iii) Coelostomidiidae paraphyletic with respect to Monophlebidae, (iv) Eriococcidae paraphyletic with respect to Stictococcidae and Beesoniidae, and (v) Aclerdidae sister to Coccidae. We recover strong support for a clade comprising Phenacoleachiidae, Pityococcidae, Putoidae, Steingeliidae and the neococcoids, along with a sister relationship between this clade and Coelostomidiidae + Monophlebidae. In addition, we recover strong support for Pityococcidae + Steingeliidae as sister to the neococcoids. Data from fossils were incomplete, and the inclusion of extinct taxa in the data matrix reduced support and phylogenetic structure. Nonetheless, these fossil data will be invaluable in DNA sequence‐based and total evidence estimates of phylogenetic divergence times.